VACCINATION POLICY AGAINST COVID 19 IN THE REPUBLIC OF SERBIA: LEGAL AND ORGANIZATIONAL ASPECTS - Mojašević, Aleksandar; Stefanović, Stefan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The subject of analysis in this paper is the current vaccination policy against COVID-19 in the Republic of Serbia, relevant legal acts related to the pandemic and vaccination, as well as the organizational structure and competence of the authorities in charge of designing and implementing this policy. The paper’s main goal is to critically review the legal framework and organization of competent authorities regarding pandemics and vaccination. The hypothesis we begin with and want to investigate is that the shortcomings of the vaccination policy in the Republic of Serbia are due, among other things, to the poor organizational structure of the authorities responsible for the policy’s design and implementation as well as inconsistent compliance with applicable regulations. In addition, vaccination policies in other countries, such as Croatia and Germany, were examined to better understand the benefits and drawbacks of the vaccination policy in Serbia. Based on the analysis of the relevant legal framework, current research and comparative findings, the general recommendation to vaccination policymaker in Serbia is that stricter and more consistent implementation of valid regulations in the field of health protection and reliance on scientifically based facts is necessary.